2013
DOI: 10.3109/0142159x.2013.789132
|View full text |Cite
|
Sign up to set email alerts
|

Teaching professionalism in medical education: A Best Evidence Medical Education (BEME) systematic review. BEME Guide No. 25

Abstract: Introduction: We undertook a systematic review to identify the best evidence for how professionalism in medicine should be taught. Methods: Eligible studies included any articles published between 1999 and 2009 inclusive. We reviewed papers presenting viewpoints and opinions as well as empirical research. We performed a comparative and thematic synthesis on all papers meeting inclusion criteria in order to capture the best available evidence on how to teach professionalism. Results: We identified 217 papers on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
187
0
20

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(225 citation statements)
references
References 120 publications
2
187
0
20
Order By: Relevance
“…Studies have demonstrated that professionalism is best learned and appreciated in long-term, context-based experiences. [16][17][18] Additionally, the term professional was not explicitly defined on the survey and was intentionally left to interpretation by the students. We hypothesize that students may have interpreted professional as being negative, rather than positive, because it distances the resident from the student and reduces the near-peer nature of the interaction, an inherent asset of the resident as teacher.…”
Section: Original Researchmentioning
confidence: 99%
“…Studies have demonstrated that professionalism is best learned and appreciated in long-term, context-based experiences. [16][17][18] Additionally, the term professional was not explicitly defined on the survey and was intentionally left to interpretation by the students. We hypothesize that students may have interpreted professional as being negative, rather than positive, because it distances the resident from the student and reduces the near-peer nature of the interaction, an inherent asset of the resident as teacher.…”
Section: Original Researchmentioning
confidence: 99%
“…Os CSBE compreendem uma abordagem pragmática interdisciplinar para solução de problemas; consiste no Naomar de Almeida-Filho, et. al. http://dx.doi.org/10.1590/1981-52712015v39n1e01842014 uso criterioso da melhor evidência científico-tecnológica disponível de forma integrada à experiência clínica 3,22 . Nessa fase, o estudante deverá desenvolver as seguintes competências: -Formular e resolver questões aplicadas à prática médica seguindo o modelo PPR, no qual o primeiro P identifica o problema, o segundo P, o fator de predição, e R é o resultado almejado.…”
Section: Quadrounclassified
“…As Oficinas compreendem avaliação sistemática de artigos científicos, a partir de discussões com docentes e pares sobre abrangência e relevância de novas publicações, focalizando a aplicabilidade no cotidiano da prática médica. Nessa atividade, os estudantes aprendem a dominar ferramentas de análise crítica de evidên-cias para usá-las na discussão de casos clínicos em reuniões de grupos e nos cuidados aos pacientes 3,4,18,23 . Além disso, completando a formação no eixo técnico-científico, seminários interdisciplinares de pesquisa em saúde abordam temas atuais de ciência e tecnologia em saúde, destacando problemas, prioridades, linhas e grupos de pesquisa em atividade, com o objetivo de avaliar o estado da arte da produção científica recente no campo da saúde.…”
Section: Práticas Integradas Em Saúde Da Família (1440 H) Supervisão unclassified
See 2 more Smart Citations